THE ROLE OF THE POLITICAL ELITE IN GOVERNMENT ADMINISTRATION AND THE CONFLICT OF INTERESTS WITHIN THE ELITE (American Journal of Pedagogical and Educational Research, 2023)
Analyzing the characteristics of the political elite, it should be noted that the relationship between the elites in government and those against it is very important in creating effective government administration and making effective decisions. This article mainly analyzes the essence and content of the concept of "Elite and political elite", their importance in the processes of government administration, especially in making political decisions, and the conflicts that arise between political elites.